Diseño del centro cultural artesanal para la parroquia San Antonio de Ibarra - López Montesdeoca, Charles José (2023)
In the process for carrying out this project, a previous urban analysis has been taken into account with the defined site where the main problem afflicting the parish has been identified, analyzing which is the best option to carry out as an intervention. We talk about the parish, initially having an introduction to it, the activities carried out, its General background, the most relevant historical data of the site. Where then we will proceed with the description of the justification, which describes a solution to the problem of San Antonio de Ibarra, defined as a study site, then we will proceed to argue about the sustenance of our project, in it the choice of said project and the delimitation of the type of equipment chosen and demonstrating the validity of said proposal. Therefore we will obtain the definition of both the general and specific objectives of the project according to the established delimitations. The districts adjacent to the study site, boundaries and a brief description will be described. To finally get to know the scope of the project what is going to be developed, marking the complexity of it with the different points to be developed. The proposal is the creation of an Artisan Cultural Center and how this will influence the Artisan, Economic and Touristcultural development of the area in addition to its quality of life and public spaces suitable for the activities carried out